The credit default swap basis - Choudhry, Moorad (Bloomberg Press, 2006)
The growth of the credit derviatives market has produced a liquid market in credit default swaps across the credit curve, and this liquidity has led many investors to access both the credit derivative and cash bond markets to meet their investment requirements. This book investigates the close relationship between the synthetic and cash markets in credit, which manifests itself in the credit default swap basis. Choudhry covers the factors that drive the basis, implications for market participants, the CDS index basis, and trading the basis. Credit market investors and traders as well as anyone with an interest in the global debt markets will find this insightful and rewarding. THIS BOOK QUALIFIES FOR 7 PD CREDITS UNDER THE GUIDELINES OF THE CFA INSTITUTE PROFESSIONAL DEVELOPMENT PROGRAM.